Engineered Serratia marcescens for efficient (3R)-acetoin and (2R, 3R)-2, 3-butanediol production. (1st May 2015) - Bai, Fangmin; Dai, Lu; Fan, Jiying; Truong, Ngoctu; Rao, Ben; Zhang, Liaoyuan; Shen, Yaling
Abstract: (3 R )-Acetoin and (2 R, 3 R )-2, 3-butanediol are important pharmaceutical intermediates. However, until now, the quantity of natural microorganisms with the ability to produce single configuration of optically pure (3 R )-acetoin and (2 R, 3 R )-2, 3-butanediol is rare. In this study, a meso -2, 3-butanediol dehydrogenase encoded by the slaC gene from Serratia marcescens MG1 was identified for meso -2, 3-butanediol and (2 S, 3 S )-2, 3-butanediol biosynthesis. Inactivation of the slaC gene could significantly decrease meso -2, 3-butanediol and (2 S, 3 S )-2, 3-butanediol and result in a large quantity of (3 R )-acetoin accumulation. Furthermore, a (2 R, 3 R )-2, 3-butanediol dehydrogenase encoded by the bdhA gene from Bacillus subtilis 168 was introduced into the slaC mutant strain of Serratia marcescens MG1. Excess (2 R, 3 R )-2, 3-butanediol dehydrogenase could accelerate the reaction from (3 R )-acetoin to (2 R, 3 R )-2, 3-butanediol and lead to (2 R, 3 R )-2, 3-butanediol accumulation. In fed-batch fermentation, the excess (2 R, 3 R )-2, 3-butanediol dehydrogenase expression strain could produce 89.81 g/l (2 R, 3 R )-2, 3-butanediol with a productivity of 1.91 g/l/h at 48 h. These results provided potential applications for (3 R )-acetoin and (2 R, 3 R )-2, 3-butanediol production.